An investigation of electromagnetic field effect on a human cell - Ismail, Mohd. Muzafar (2010)
The interaction between electromagnetic waves and human cell has received renewed attention recently. This interaction can come from many sources such as cellular phone, the increased clinical application of magnetic resonance imaging (MRI) procedures, radio base station, power line, lightening and x ray radiation. The structure of a human cell will be studied from many school of taught such as biochemical in cell, cytoplasm, nucleus and membrane. The understanding obtained will be used as the basis in the developing of mathematical model. It understood from various researchers that when radiation enters to human body, the component of the cell will react through kinetic energy. The main objective of this project is to analyze the behavior and determine the parameters of the interaction in a single cell when expose to electromagnetic wave such as the attenuation coefficient. The outcome of this project will give an understanding about propagation of electromagnetic wave in human skin cell The Maxwell equations will be used as the basis of the modeling in this project with the aid of numerical method approaches specifically Finite Difference Time Domain (FDTD) techniques. To develop the model MATLAB tool will be used. Results obtained from the developed model will be verified with known result obtained from other researchers.